Use of Antidepressant and Anxiolytic Drugs in Scandinavian Countries between 2006 and 2021: A Prescription Database Study - Bojanić, Ivana (Depression and Anxiety, 2024)
Introduction. The use of antidepressant and anxiolytic drugs has changed in Scandinavian countries over recent decades, with notable national variations. Objective. To describe and compare antidepressant and anxiolytic drug use in Norway, Sweden, and Denmark. Methods. Data included each country’s prescription registers from 2006 to 2021. The measures were period (1-year) prevalence (users per 1000 inhabitants) and therapeutic intensity (TI; daily defined dose (DDD) per 1000 inhabitants per day), overall, by drug classes and age groups. Results. The prevalence of antidepressant use increased from 2006 to 2021 and was highest in Sweden (78 to 107 users per 1000 inhabitants) and lowest in Norway (61 to 69 users per 1000 inhabitants). The prevalence of anxiolytic use decreased, most steeply in Denmark (50 to 18 users per 1000 inhabitants). The TI of antidepressants increased consistently in Norway and Sweden, but more variably in Denmark. Sweden had the highest increase in TI of antidepressants (56%). The TI of anxiolytics declined most markedly in Denmark (by 75%). The prevalence of antidepressant and anxiolytic use was highest among adults ≥65 years. The prevalence of antidepressant use increased across age groups in Sweden and young people (5-19 years) in Norway, but not in Denmark. Conclusions. The use of antidepressants increased in Scandinavia in 2006-2021, but decreased for anxiolytics, with country variations in the number of users and the amount used. Future research should target factors underlying high antidepressant and anxiolytic use in older adults across countries and increasing antidepressant use in Sweden and among young Norwegians.